Web-based supply chain system design using blockchain - Faris Nofandi; Muhammad R.B. Janaputra; Rizki A. Pratama (Journal of Transport and Supply Chain Management)
Background: This research aims to design an agromaritime supply chain system as a development of blockchain technology in Industry 4.0.